Beyond the North-South Debate: The Global Significance of Sustainable Development Debates in South Korea - Pak, Michael S. (Problemy Ekorozwoju, 2015)
While debates on sustainable development have traditionally pitted the developing countries of the global South against the industrialized countries of the North, this essay addresses possible new elements in the so-called North-South debate, mainly by examining it from the perspective of a former developing country that has recently succeeded in becoming a developed industrial economy. Having achieved rapid economic growth that has been described as miraculous, South Korea has come to enjoy the reputation of being a country that has also shown a firm commitment to sustainable development, and in 2012,was even chosen over Germany to host the headquarters of the UN Green Climate Fund. Yet within the country the Korean government has been subject to ongoing criticism as still placing a preponderant emphasis on economic growth, while largely ignoring the ecological and social aspects of sustainable development. While not disagreeing with the critics, this essay shifts the focus away from the local causes of the alleged inconsistences and lapses in the Korean government’s sustainable development policy, and uses the Korean case as a prism through which to view the global trends that since the early 1990s have emerged as major obstacles in making sustainable development possible in fact, not just in words. Building on Thomas Piketty’s near definitive study of the rise of income inequality and oligarchic ownership of much of the world’s wealth in the aftermath of the neoliberalist triumph of the 1980s, the essay identifies South Korea as the epitome of a country whose economy has come to be controlled to a large extent by the global financial elite, and suggests that beyond the rhetoric, its development policy has reflected the predominantly growth-oriented agenda of such elite. The implication throughout is that, should the current trends continue, the Korean case may well provide a good indication of what is further to come as today’s rapidly industrializing economies also begin to mature.